Fucoidan-degrading fungal strains: screening, morphometric evaluation, and influence of medium composition - Rodríguez-Jasso, Rosa María (2010)
Ten different fungal strains from the genus Aspergillus, Penicillium, and Mucor were screened for fucoidan hydrolyzing ability aiming to find microorganisms able to produce sulfated fucan-degrading enzymes. Screening was carried out by measuring the strains kinetic and morphometric behavior over plate assays using Laminaria japonica fucoidan as only carbon source, testing three nitrogen sources (urea, peptone, and sodium nitrate). The selected fungal strains were subsequently used in submerged fermentations, which were performed for (1) selection of the strains able to growth over fucoidan medium and (2) media selection, testing the synergy of fucoidan with other sugars for inducing high enzyme titles. Radial expansion and hyphae parameters were observed for Aspergillus niger PSH, Mucor sp. 3P, and Penicillium purpurogenum GH2 grown only over fucoidan-urea medium. A. niger PSH showed the maximum enzymatic activity values, which were significantly different (p<0.05) from those achieved by the other selected fungi. Sucrose addition to fucoidan media proportioned the highest fucoidanase activity values for this fungal strain. This research allowed establishing optimal conditions for metabolites synthesis by fungal stains able to act toward fucoidan ramified matrix.